Quality indicators and performance measures for prison healthcare: a scoping review - Bellass, Sue; Canvin, Krysia; McLintock, Kate; Wright, Nat; Farragher, Tracey; Foy, Robbie; Sheard, Laura (Health & justice, 2022)
Background Internationally, people in prison should receive a standard of healthcare provision equivalent to people living in the community. Yet efforts to assess the quality of healthcare through the use of quality indicators or performance measures have been much more widely reported in the community than in the prison setting. This review aims to provide an overview of research undertaken to develop quality indicators suitable for prison healthcare. Methods An international scoping review of articles published in English was conducted between 2004 and 2021. Searches of six electronic databases (MEDLINE, CINAHL, Scopus, Embase, PsycInfo and Criminal Justice Abstracts) were supplemented with journal searches, author searches and forwards and backwards citation tracking. Results Twelve articles were included in the review, all of which were from the United States. Quality indicator selection processes varied in rigour, and there was no evidence of patient involvement in consultation activities. Selected indicators predominantly measured healthcare processes rather than health outcomes or healthcare structure. Difficulties identified in developing performance measures for the prison setting included resource constraints, data system functionality, and the comparability of the prison population to the non-incarcerated population. Conclusions Selecting performance measures for healthcare that are evidence-based, relevant to the population and feasible requires rigorous and transparent processes. Balanced sets of indicators for prison healthcare need to reflect prison population trends, be operable within data systems and be aligned with equivalence principles. More effort needs to be made to meaningfully engage people with lived experience in stakeholder consultations on prison healthcare quality. Monitoring healthcare structure, processes and outcomes in prison settings will provide evidence to improve care quality with the aim of reducing health inequalities experienced by people living in prison.